Unconventional monetary policy and real estate sector: a financial dynamic computable general equilibrium model for Italy. Issue 2 (2nd April 2020) - Ahmed, Irfan; Socci, Claudio; Severini, Francesca; Pretaroli, Rosita; Al Mahdi, Hassan Kasady
Abstract : This study investigates the effects of an expansionary monetary policy on the Italian economy and, in particular, on real estate (RE) as a commodity. RE is a key sector for the Italian economy. It has strong interactions with the other sectors, especially with the financial markets. Therefore, we develop a financial dynamic computable general equilibrium model to analyze the response of RE sector to a shock on money supply. The parameters of the model are calibrated on the financial social accounting matrix for Italy that identifies the economic and financial flows in the economic system in a well-defined time period. Our findings confirm that the policy has a positive impact on real economy and on the RE output, value added and pricing.